Studi Perbandingan Kualitas Layanan Pantai Manggar dan Lamaru di Kota Balikpapan dengan Motode SERVQUAL - Bambang Jati Kusuma; Syahrul Karim; Yogiana Mulyani (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
About 80 percent of the management of tourist attractions in Balikpapan and East Kalimantan are generally managed by local governments while 20 percent are only managed by the private sector. This study aims to determine the quality of tourism management services managed by local governments with the private sector with a case study of the attractions of Manggar and Lamaru beaches. Manggar Beach is managed by Disporapar Balikpapan (public sector), while Lamaru Beach is managed by the private sector (private sector). The hypothesis in this study is that the quality of Lamaru beach services is better than Manggar beach. This study uses a comparative method (comparison) by measuring SERVQUAL dimensions; Tangibles, Reliability, Responsiveness, Assurance, and Empathy with 25 instruments. The instrument used in this study is intended to produce accurate data using a Likert scale. The number of respondents is 150 people who are domestic tourists as long as they have visited the two attractions. As a result, the quality of Lamaru beach services is far better than Manggar beach for all SERVQUAL dimensions